Combining ability and heterosis of untested inbred lines in sunflower (Helianthus annuus L.): Combining ability and heterosis of untested inbred lines in sunflower (Helianthus annuus L.) - M S UMA; S N MANOHARA; S D NEHRU (Journal of Oilseeds Research, 2020)
An investigation was carried out to estimate the combining ability and heterosis of 12 fertile sunflower hybrids, 12 parents and checks viz., KBSH 44 and KBSH 53 in augmented design during kharif 2018. The lines CMS 903A, NDCMS 2A and the tester K 3 were identified as good general combiners for seed yield and its component traits. The cross combinations CMS 903A × GMU 411, CMS 135A × GMU 411 and NDCMS 2A × GMU 411 exhibited highest significant sca effects and high heterosis over checks for seed yield.